Beta arrestin 1 is a key regulator of pulmonary vascular tone - Leonard F. Lebender; Alexander Seidinger; Michaela Matthey; Birte Dyck; Christian Schlamm; Abdullah Kaddoura; Maximilian Hausherr; Britta Eggers; Katrin Marcus; Evi Kostenis; Volkmar Gieselmann; Michael Adamzik; et al. (Proceedings of the National Academy of Sciences, 2026)
Pulmonary arterial hypertension (PAH) is a serious disorder, in which increased vascular tone is one of the critical hallmarks. Since beta arrestins (bArrs) have been shown to regulate smooth muscle tone in the airways, we investigated the function of bArr1 in the pulmonary vasculature. Here, we report that bArr1 is essential for maintaining normal pulmonary arterial tone. Specifically, pulmonary arteries from bArr1−/− mice exhibited reduced NO-dependent vasorelaxation due to impaired soluble guanylyl cyclase (sGC) activity, which was restored by the heme-independent sGC activator BAY58-2667. We identified bArr1 as a binding partner of sGC and the sGC heme reductase cytochrome b5 reductase (Cyb5r3), indicating that bArr1 is vital for sensitizing sGC to NO. Finally, mice with either ubiquitous or smooth muscle-specific bArr1 deficiency developed pulmonary hypertension (PH). These findings highlight the important role of bArr1 in regulating pulmonary vascular tone and propose it as a potential therapeutic target for the treatment of PH.